TXD173: Textile Design / College of Creative Arts - UiTM, College of Creative Arts (2023)
A study of Textile Design provides students with broad knowledge of the properties, performance and uses of textile in which resist, fiber and printing are explored. Textile designs will give students the opportunity to be creative, independent learners and to explore functional and aesthetic aspects of textiles, demonstrate responsibility in decision making and encourage individuals to express ideas and opinions.